IMPROVING APPROACHES TO FUNCTION OF MECHANISMS OF STATE REGULATION OF THE DEVELOPMENT OF ELECTRICAL ENERGY SECTOR - Ievdolimov V.A. (Pressing Problems of Public Administration, 2015)
The article says about the scientific theoretical approaches to improving of state regulationof the development of electrical energy sector in Ukraine in context international experience.